Identification of active compounds and anti-acne activity from extracts and fractions of surian (Toona sinensis) leaves planted in Sumedang, West Java, Indonesia - ERISA FEBRIYANI; SYAMSUL FALAH; DIMAS ANDRIANTO; TIEN LASTINI (Society for Indonesian Biodiversity, 2018)
Febriyani E, Falah S, Andrianto D, Lastini T. 2018. Identification of active compounds and anti-acne activity from extracts and fractions of surian (Toona sinensis) leaves planted in Sumedang, West Java, Indonesia. Biodiversitas 19: 1406-1412. Surian or toon (Toona sinensis Merr) leave is one of the herbs containing many bioactive compounds as potential sources of anti-acne agents. The aim of this work is to identify and evaluate the anti-acne activity of Surian leaves extract and fractions against acne bacteria. Crude extracts of Surian leaves from various solvents (methanol, ethanol, and ethyl acetate) were screened for their antimicrobial activity using disc diffusion. The results showed that ethyl acetate extract demonstrated the highest inhibition against Propionibacterium acne (49.93%), Staphylococcus epidermidis (57.14%), Staphylococcus aureus (18.93%), and Eschericia coli (82.03%). The results of Brine Shrimp Lethality Test (BSLT) showed that the methanol extract had the highest cytotoxicity of LC50 at 29.76 ?g/mL. The extract was then fractionated using column chromatography, resulted in 6 fractions. The fraction 3 showed the best antibacterial effect against P. acne (28.27%), S. epidermidis (7.38%) and S. aureus (10.38%). Minimum inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) test were carried out using liquid dilution, whereas dimethyl sulfoxide (DMSO) and Clindamycin were used as a negative and positive control, respectively. The MIC and MBC test assays of fraction 3 varied for different bacteria P. acne bacteria (5000 and 5000 ppm), S. aureus (1250 and 10000 ppm), E. coli (2500 and 5000 ppm), while for S. epidermidis the fraction 3 was able to inhibit with MIC value of 5000 ppm. Based on microscopic observation using Scanning Electron Microscope (SEM), the fraction 3 at the dose of 5000 ppm could promote the cellular destruction of P. acne. Further experiment using Liquid Chromatography-Tendem Mass Spectrometry (LC-MS/MS) showed various compounds associated with the anti-acne activity of the fraction 3, such as pheophorbide a, pheophytin a and dihomo-?-linolenic acid.